2018
DOI: 10.15298/invertzool.15.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Glair glands and spawning in unmated crayfish: a comparison between gonochoristic slough crayfish and parthenogenetic marbled crayfish

Abstract: In the period before spawning, freshwater crayfish females develop glair glands on the underside of the pleon. These glands produce the mucus for a gelatinous tentlike structure in which the eggs are fertilized and attached to the pleopods. Long-term observation of females of the sexually reproducing slough crayfish, Procambarus fallax, kept in captivity revealed that the glair glands developed in late winter and late summer of each year independently of the presence of males. In mated females, they secreted t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Body weight measurements were taken before feeding. At the end of the experiment (100 days), the animals were starved for one day, their final body weight was taken (Supplementary information Table S6 ) and the presence of glair glands and attached eggs were visually noticed 21 . For categorization of crayfish females reproduction, see Supplementary information Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body weight measurements were taken before feeding. At the end of the experiment (100 days), the animals were starved for one day, their final body weight was taken (Supplementary information Table S6 ) and the presence of glair glands and attached eggs were visually noticed 21 . For categorization of crayfish females reproduction, see Supplementary information Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These traditionally used ornamental fish feeds are often deficient in certain nutrients, so growth can be slower 4 , 5 , causing micronutrient deficiencies 20 and generational turnover may take longer. Although efforts have been made to understand preferences for amino acids in marbled crayfish 16 (see our previous study 5 ), research is yet to explore the preferences for fatty acids that affect the speed at which maturation and accompanied glair gland formation appear 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Glair glands express themselves as a white substance underneath the female's abdomen during the mating season. These areas of white appear weeks before reproduction and continue to become more distinct throughout the mating season, which makes glair glands an indicator of future reproduction (Vogt, 2018). In total, we collected 62 adult female F. obscurus in our study: 33 in reproductive form and 29 in nonreproductive form.…”
Section: Methodsmentioning
confidence: 99%
“…Before extruding eggs, female crayfishes express white glair glands on the ventral portion of their abdomens, which secrete a glue‐like substance (glair) which binds eggs to the underside of the pleon. Glair can be used as an indicator of the reproductive seasons (and therefore reproductive form) of crayfishes (Vogt, 2018). Separate studies on two different species of crayfish ( Procamabrus clarkii and Pacifastacus leniusculus ) demonstrated that reproductive form females, like males, also wield relatively larger claws compared to nonreproductive females (Buřič et al, 2010; Hamasaki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A long-term experiment with 6 females of P. fallax in the laboratory of G.V. revealed one to two spawnings per year and a maximum of three spawnings per lifetime (Vogt, 2018c). The population trends in the Everglades suggest a similar 5-7 month pause between reproductive events (van der Heiden & Dorn, 2017).…”
Section: Reproduction and Fertilitymentioning
confidence: 99%